Mutualism between the sea anemone Antholoba achates (Drayton, 1846) (Cnidaria: Actiniaria: Actinostolidae) and the spider crab Libinia spinosa Milne-Edwards, 1834 (Crustacea: Decapoda, Majidae) - Acuña, Fabian Horacio (2003)
In this paper the association (mutualism) betrween the sea anemone Antholoba achates and the spider crab Libinia spinosa is described.